Deconstructing dogma: Nonoperative management of small bowel obstruction in the virgin abdomen. Issue 1 (July 2018) - Collom, Morgan L.; Duane, Therese M.; Campbell-Furtick, Mackenzie; Moore, Billy J.; Haddad, Nadeem N.; Zielinski, Martin D.; Ray-Zack, Mohamed D.; Yeh, Daniel D.; Choudhry, Asad J.; Cullinane, Daniel C.; Inaba, Kenji; Escalante, Agustin; et al.
Abstract : BACKGROUND: Management of small bowel obstruction (SBO) has become more conservative, especially in those patients with previous abdominal surgery (PAS). However, surgical dogma continues to recommend operative exploration for SBO with no PAS. With the increased use of computed tomography imaging resulting in more SBO diagnoses, it is important to reevaluate the role of mandatory operative exploration. Gastrografin (GG) administration decreases the need for operative exploration and may be an option for SBO without PAS. We hypothesized that the use of GG for SBO without PAS will be equally effective in reducing the operative exploration rate compared with that for SBO with PAS. METHODS: A post hoc analysis of prospectively collected data was conducted for patients with SBO from February 2015 through December 2016. Patients younger than 18 years, pregnant patients, and patients with evidence of hypotension, bowel strangulation, peritonitis, closed loop obstruction or pneumatosis intestinalis were excluded. The primary outcome was operative exploration rate for SBO with or without PAS. Rate adjustment was accomplished through multivariate logistic regression. RESULTS: Overall, 601 patients with SBO were included in the study, 500 with PAS and 101 patients without PAS. The two groups were similar except for age, sex, prior abdominal surgery including colon surgery, prior SBO admission, and history of cancer. Multivariate analysis showed that PAS (odds ratio [OR], 0.47; p = 0.03) and the use of GG (OR, 0.11; p < 0.01) were independent predictors of successful nonoperative management, whereas intensive care unit admission (OR, 16.0; p < 0.01) was associated with a higher likelihood of need for operation. The use of GG significantly decreased the need for operation in patients with and without PAS. CONCLUSIONS: Patients with and without PAS who received GG had lower rates of operative exploration for SBO compared with those who did not receive GG. Patients with a diagnosis of SBO without PAS should be considered for the nonoperative management approach using GG. LEVEL OF EVIDENCE: Therapeutic, level IV.